Ambiguitas Penerapan Prinsip Ekonomi Islam dalam Pengentasan Kemiskinan di Aceh - Misbah, T Lembong (Program Studi Kesejahteraan Sosial Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Ar-Raniry, 2025)
This article explores the ambiguity between the ideal principles of Islamic economics and the socio-economic realities in Aceh. Although Aceh is recognized as the only province in Indonesia that officially implements Islamic Sharia, the region's socio-economic conditions reveal relatively high poverty rates and evident economic inequality. This study aims to identify the causes behind the discrepancy between Islamic economic principles—such as justice, the prohibition of usury (riba), and wealth distribution—and the economic activities and public policies applied in Aceh. The research adopts a qualitative approach using descriptive-analytical methods, based on secondary data and academic literature. The findings indicate that the implementation of Islamic economics in Aceh remains largely symbolic and has yet to address deeper structural aspects. Several factors contribute to this ambiguity, including limited understanding of Islamic economic literacy, lack of coordination between religious scholars (ulama) and the government, and ineffective zakat management. This article suggests the need for institutional reform, improved economic literacy, and relevant Islamic economic innovations as steps toward a more authentic and empowering implementation of Islamic economics in society